COACHING EFFORTS FOR TERRORISM PRISONERS IN THE PERSPECTIVE OF INDONESIAN POSITIVE LAW - Januar Rahman Mutiara; Fokky Fuad Wasitaatmadja (Asosiasi Dosen Muda Indonesia, 2024)
The crime of terrorism is a serious crime that requires special guidance methods in handling it. Efforts to handle terrorism cases in Indonesia are carried out through special approaches, namely a hard and a soft approaches. Deradicalization is an action that seeks to develop the mentality of national and religious ideology. This research is empirical legal research that examines Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. The research method applied is descriptive, which aims to describe the actual situation. This data is then analyzed using a quantitative approach, which means the data is analyzed selectively and described before finding a solution to the problem. This data was analyzed to determine the effects of implementing guidance according to Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. Efforts to deal with Based on the evidence, it can be concluded that those who commit terrorist crimes in Indonesia are generally quite good. The obtained data shows that former prisoners in terrorism cases in Indonesia have returned to be good citizens. Although Indonesia is making good efforts to combat terrorism, much more needs to be improved. The government, law enforcement agencies and society have to work together in fighting terrorism and avoiding cases of terrorism in the future.